Effects of alfalfa meal on quality and function of pork meatballs. Issue 8 (5th April 2022) - Xu, Zhifeng; Du, Yushuang; Li, Na; Geng, Hongmin; Ali, Qasim; Li, Xinbo; Gao, Yajun; Wang, Yan; Xing, Ronghui; Wu, Jie; Cui, Fangjie; Wang, Chengzhang; et al.
Abstract: Alfalfa ( Medicago sativa L.) is abundant in dietary fiber, alfalfa saponins, and other active ingredients. However, the application of alfalfa is scarce in food. Meatball is one of the most popular meat products in daily life, but eating too many meatballs could result in obesity, hyperlipidemia, and other diseases. With increasing attention to healthy diet, how to keep the original color, aroma, taste, and shape of food with low fat and nutrition has become an urgent problem to be solved. In this study, different amounts of alfalfa meal or extruded alfalfa meal were added to pork meatballs to explore the optimal adding ratio of two kinds of alfalfa meal in pork meatballs. Further animal experiments were conducted for two weeks to prove the efficacy of two kinds of alfalfa balls in lowering blood lipid and body weight. The results showed that 0.5% alfalfa meal and 1% extruded alfalfa meal could improve the quality of prepared pork meatballs. Animal experiments demonstrated that two kinds of alfalfa meal pork meatballs had a good effect of reducing blood lipid, and the alfalfa meal pork meatballs had a better effect on reducing serum cholesterol and average daily weight gain of mice. This study provided a theoretical basis for making healthy and nutritious pork meatballs, which could provide more delicious food for people, especially people who are obese and the elderly. Abstract : To keep the original color, aroma, taste, and shape of food with low fat and nutrition, alfalfa meal or extruded alfalfa meal was applied to pork meatballs. The research demonstrated that alfalfa meal could improve the quality of prepared pork meatballs and have a good effect on reducing blood lipid and body weight of mice.